RELACIÓN ENTRE LOS NIVELES DE SEDENTARISMO, DE OXIGENACIÓN Y EL ÍMC DE UN GRUPO DE ADMINISTRATIVOS DE UN CENTRO REGIONAL UNIVERSITARIO UBICADO EN LA PROVINCIA DE VERAGUAS. AÑO 2023 (Fiep Bulletin - online, 2024)
Professionals, especially those who work in the administrative part, in higher education institutions, usually spend approximately 8 hours or more in sedentary positions. The time they spend performing their job duties can generate stressful situations, alter their lifestyle or can be a factor that determines the time that the person can dedicate to carrying out activities that keep them physically active. The fundamental purpose of this study was to measure the level of sedentary lifestyle, relating it to BMI and oxygenation levels in a group of administrators who work in a regional university center belonging to a public university located in the district of Santiago, province of Veraguas, in the year 2023. The sample was made up of 126 administrative staff. To collect the information, the Pérez Rojas García Test was used, which consists of: going up and down a 25 cm step, heart rate (monitored at the beginning, during the test and at the end of each of the cycles), oximeters to measure oxygenation levels, stopwatches to measure the time of each load. The heart rate measured in 15 seconds multiplied by 4 was used as a control parameter.